On the development of an open platform for m-government services - Rodrigues, Helena (2005)
Citizens and local government services are often not as well connected as they ideally should be. Services may not be well advertised or may simply be cumbersome or time-consuming to access. In this paper we present our ongoing work in investigating how to better connect the citizen with their local government with the support of context-aware applications. We describe a set of user requirements for m-government services and open service-oriented platforms. In particular, we analyze the requirements and present the research issues on a context modeling component for supporting context-aware service discovery. Our motivation to develop it is driven by the need to provide appropriate local government services in an easily accessible manner whenever and wherever they may be needed